Capitalist restructuring and the Pacific Rim - Palat, Ravi Arvind (RoutledgeCurzon, 2004)
This book situates the evolution of the high growth economies along Asia's Pacific Rim after the Second World War within broader global political and economic changes.
Keywords: Pacific Area -- Economic conditions.; Financial crises -- Pacific Area.; Structural adjustment (Economic policy) -- Pacific Area.; Pacific Area -- Economic integration.; United States -- Foreign economic relations -- East Asia.; East Asia -- Foreign economic relations -- United States.; Pacifique, Région du -- Conditions économiques.; Ajustement structurel (Économie) -- Pacifique, Région du.; Pacifique, Région du -- Intégration économique.; POLITICAL SCIENCE -- Economic Conditions.; BUSINESS & ECONOMICS -- Economics -- Comparative.; BUSINESS & ECONOMICS -- Economic Conditions.; BUSINESS & ECONOMICS -- Economic History.; Economic history; Financial crises; International economic integration; International economic relations; Structural adjustment (Economic policy); East Asia; Pacific Area; United States